2015
DOI: 10.1371/journal.pone.0130843
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Subcutaneous versus Submuscular Transposition of the Ulnar Nerve for Cubital Tunnel Syndrome: A Systematic Review and Meta-Analysis

Abstract: ObjectiveTo pool reliable evidences for the optimum anterior transposition technique in the treatment of cubital tunnel syndrome by comparing the clinical efficacy of subcutaneous and submuscular anterior ulnar nerve transposition.MethodsA comprehensive search was conducted in PubMed MEDLINE, Cochrane Library, EMBASE, Web of Science, OVID AMED, EBSCO and potentially relevant surgical archives. Risk of bias of each included studies was evaluated according to Cochrane Handbook for Systematic Reviews of Intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Multiple operative solutions exist for cubital tunnel syndrome but none have been shown to be significantly superior in the short-or long-term with regard to complications or clinical resolution of symptoms. [21][22][23][24][25][26][27] Some authors have suggested that a custom intraoperative approach should be tailored to each individual patient based on their own anatomy. 28 Unusual findings like those presented in this report further support a tailored intraoperative approach.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple operative solutions exist for cubital tunnel syndrome but none have been shown to be significantly superior in the short-or long-term with regard to complications or clinical resolution of symptoms. [21][22][23][24][25][26][27] Some authors have suggested that a custom intraoperative approach should be tailored to each individual patient based on their own anatomy. 28 Unusual findings like those presented in this report further support a tailored intraoperative approach.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to perform a submuscular transposition was made because of thickening of the nerve and osteoarthrosis changes caused by elbow fracture-dislocation, which could be a risk factor for early recurrence of ulnar nerve entrapment. Furthermore, the literature does not provide conclusive evidence either for or against any technique, 9 so anterior submuscular transposition was performed according to the surgeon's preference.…”
Section: Discussionmentioning
confidence: 99%
“…Although various rating systems for improvement exist, these have not been universally adopted. 21 A reliable and well-validated composite measure could be constructed using "Area under the Receiver Operating Characteristic" (ROC) curve. 22 Composite measure 23 in statistics and research design refer to combining multiple individual measures of various outcome parameters 24 that are assumed to be associated with variation in diagnostic accuracy.…”
Section: Evaluation Of Surgical Methods For Treatment Of Cubital Tunnmentioning
confidence: 99%